2014
DOI: 10.3148/75.1.2014.7
|View full text |Cite
|
Sign up to set email alerts
|

Dietitians’ Perceptions of Precepting: Knowledge, Skills, Attitudes, Barriers, and Training

Abstract: The findings articulate the KSA, training needs, and barriers to precepting considered significant for dietitian preceptors. The results are important for the advocacy for resources to support the training and development of preceptors, upon whom sustainability of the profession depends.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 18 publications
2
33
0
Order By: Relevance
“…The overall high self-perceptions of national preceptors' KSAs indicate that regardless of the training, they can precept interns, which was consistent with results from another study 18. From this study, more than 50% of the national and local preceptors had practiced for greater than 10 years and 75% of the national and local preceptors had precepted for more than 3 years.…”
Section: Discussionsupporting
confidence: 89%
“…The overall high self-perceptions of national preceptors' KSAs indicate that regardless of the training, they can precept interns, which was consistent with results from another study 18. From this study, more than 50% of the national and local preceptors had practiced for greater than 10 years and 75% of the national and local preceptors had precepted for more than 3 years.…”
Section: Discussionsupporting
confidence: 89%
“…Studies were from the USA, [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Australia, 14,[35][36][37][38][39][40][41][42][43] Canada, 28,[44][45][46][47][48] the UK, [49][50][51][52] South Africa 53 and Nigeria. 54 Professions represented included physiotherapy, 15,19,21,27,29,31,33,36,38,45,…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen papers used quantitative methods for investigating effective CE behaviours, with all using surveys asking participants to rate CE behaviours, usually related to perceived importance (Table S1). Five studies derived the content of the survey question from the literature, 15,17,19,22,44 six were based on pre-existing instruments, 14,18,20,23,53,54 two were derived from the literature and student feedback, 50,51 one from student feedback, 16 from previous surveys 49 and three were derived from both the literature and pre-existing instruments. 35,36,53 Descriptions of effective CE skills and attributes were identified by students' and educators' perceptions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They serve as educators, mentors, and role models and should ideally possess both clinical and teaching skills (5). Although preceptors typically receive substantial clinical training, research has shown that most preceptors undergo suboptimal education in teaching and learning methods, assessment, and provision of feedback to students (6,7). whereas other programs deliver their own preceptor training workshops in response to the needs raised by the preceptors.…”
Section: Introductionmentioning
confidence: 99%